A small molecule that binds and inhibits the ETV1 transcription factor oncoprotein - Pop, Marius S (2014)
Members of the ETS transcription factor family have been implicated in several cancers, where they are often dysregulated by genomic derangement. ETS variant 1 (ETV1) is an ETS factor gene that undergoes chromosomal translocation in prostate cancers and Ewing's sarcomas, amplification in melanomas, and lineage dysregulation in gastrointestinal stromal tumors. Pharmacologic perturbation of ETV1 would be appealing in these cancers; however, oncogenic transcription factors are often deemed “undruggable” by conventional methods. Here, we used small-molecule microarray (SMM) screens to identify and characterize drug-like compounds that modulate the biological function of ETV1. We identified the 1,3,5-triazine small molecule BRD32048 as a top candidate ETV1 perturbagen. BRD32048 binds ETV1 directly, modulating both ETV1-mediated transcriptional activity and invasion of ETV1-driven cancer cells. Moreover, BRD32048 inhibits p300-dependent acetylation of ETV1, thereby promoting its degradation. These results point to a new avenue for pharmacological ETV1 inhibition and may inform a general means to discover small molecule perturbagens of transcription factor oncoproteins.